Sumoylation Protects Against β-Synuclein Toxicity in Yeast - Popova, Blagovesta; Kleinknecht, Alexandra; Arendarski, Patricia; Mischke, Jasmin; Wang, Dan; Braus, Gerhard H. (Frontiers in Molecular Neuroscience, 2018)
Aggregation of α-synuclein plays a central role in the pathogenesis of Parkinson's disease (PD). The budding yeast Saccharomyces cerevisiae serves as reference cell to study the interplay between α-synuclein misfolding, cytotoxicity and posttranslational modifications. The synuclein family includes α, β and γ isoforms. β-synuclein (βSyn) and α-synuclein (αSyn) are found at presynaptic terminals and both proteins are presumably involved in disease pathogenesis. Similar to αSyn, expression of βSyn leads to growth deficiency and formation of intracellular aggregates in yeast. Co-expression of αSyn and βSyn exacerbates the cytotoxicity. This suggests an important role of βSyn homeostasis in PD pathology. We show here that the small ubiquitin-like modifier SUMO is an important determinant of protein stability and βSyn-induced toxicity in eukaryotic cells. Downregulation of sumoylation in a yeast strain, defective for the SUMO-encoding gene resulted in reduced yeast growth, whereas upregulation of sumoylation rescued growth of yeast cell expressing βSyn. This corroborates a protective role of the cellular sumoylation machinery against βSyn-induced toxicity. Upregulation of sumoylation significantly reduced βSyn aggregate formation. This is an indirect molecular process, which is not directly linked to βSyn sumoylation because amino acid substitutions in the lysine residues required for βSyn sumoylation decreased aggregation without changing yeast cellular toxicity. αSyn aggregates are more predominantly degraded by the autophagy/vacuole than by the 26S ubiquitin proteasome system. We demonstrate a vice versa situation for βSyn, which is mainly degraded in the 26S proteasome. Downregulation of sumoylation significantly compromised the clearance of βSyn by the 26S proteasome and increased protein stability. This effect is specific, because depletion of functional SUMO did neither affect βSyn aggregate formation nor its degradation by the autophagy/vacuolar pathway. Our data support that cellular βSyn toxicity and aggregation do not correlate in their cellular impact as for αSyn but rather represent two distinct independent molecular functions and molecular mechanisms. These insights into the relationship between βSyn-induced toxicity, aggregate formation and degradation demonstrate a significant distinction between the impact of αSyn compared to βSyn on eukaryotic cells.